Uma contribuição ao estudo do dimensionamento de motores e de um sistema de irrigação por gotejamento - Teixeira, Tiago de Souza (2014)
This dissertation aims to study and develop routines for calculating the sizing of drip irrigation systems, focusing on the motor-pump set. To develop this study we chose to use of Octave software, where the routines were programmed. The program developed from the selected culture is capable of sizing the network of pipes, from the sideline, where drippers are installed to the suction line. It is estimated the power that the motor-pump set must provide to the system and the motor rated power able to meet the requirements of the installation is also determined. With the design complete, it is possible to forecast operating time of the system as well as energy costs to be expended in the operation.